1999
DOI: 10.1016/s0735-1097(99)00023-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thrombin generation by simvastatin and lack of additive effects of aspirin in patients with marked hypercholesterolemia

Abstract: In men with hypercholesterolemia, lowering serum cholesterol level by a three-month simvastatin treatment is accompanied by a marked reduction of thrombin generation both at basal conditions in venous blood and after activation of hemostasis by microvascular injury. Once blood cholesterol became reduced, adding aspirin to simvastatin did not enhance dampening of thrombin formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0
6

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 24 publications
2
99
0
6
Order By: Relevance
“…Several studies have shown that statins reduce circulating levels of F1 ϩ 2 (15,16) and F1 ϩ 2 in samples from bleeding time wounds in patients with hypercholesterolemia (17,18). Aoki et al (19) showed that increased platelet-dependent thrombin generation in hypercholesterolemic patients normalizes after pravastatin treatment, whereas Szczeklik et al (17) found that simvastatin inhibits thrombin formation in bleeding time blood. Aspirin had no further effect on thrombin formation.…”
Section: -The Reduction Of Vwfag Was ϫ53% After Pravastatin Treatmenmentioning
confidence: 99%
“…Several studies have shown that statins reduce circulating levels of F1 ϩ 2 (15,16) and F1 ϩ 2 in samples from bleeding time wounds in patients with hypercholesterolemia (17,18). Aoki et al (19) showed that increased platelet-dependent thrombin generation in hypercholesterolemic patients normalizes after pravastatin treatment, whereas Szczeklik et al (17) found that simvastatin inhibits thrombin formation in bleeding time blood. Aspirin had no further effect on thrombin formation.…”
Section: -The Reduction Of Vwfag Was ϫ53% After Pravastatin Treatmenmentioning
confidence: 99%
“…Although the underlying mechanism remains undetermined, statins inhibit fibrinogen expression and thrombin formation in vitro and reduce platelet aggregation and deposition in diseased vessels in vivo. [83][84][85][86][87][88][89] Reduced expression of cyclooxygenase 2 (COX-2), thromboxane A 2 (TxA 2 ), or TxB 2 and enhanced synthesis of prostacyclin caused by statin treatment may contribute to diminished platelet activation. 90 -92 Statins may also regulate other aspects of the inflammatory response underlying atherogenesis, including endothelial vasodilatation via enhanced expression of endothelial nitric oxide synthase (eNOS), reduced blood viscosity, and diminished oxidative modification of LDL via their potential antioxidant properties.…”
mentioning
confidence: 99%
“…4 There is evidence for antithrombotic effects of statins. 5,6 Proposed mechanisms of antithrombotic actions are inhibition of thrombin signaling, 7 prevention of LDL oxidation, 8 upregulation of endothelial NO synthase, 9,10 downregulation of platelet-induced upregulation of monocyte tissue factor expression, 11 and induction of CD39/ATPdase in thrombinactivated endothelial cells. 12 Agents that are released from activated platelets and injured cardiovascular cells have been recognized as major factors in the development of thrombosis.…”
mentioning
confidence: 99%
“…21 Simvastatin (SVN) treatment resulted in normalization of altered platelet aggregation and reduced the thromboxane-metabolite excretion. 6,7 As clinical benefits of statins are evident even in patients receiving aspirin, 6 reduction in thromboxane per se is unlikely to be the explanation for antithrombotic effects. Indirectly, modification of endothelial function may alter platelet activity, 12,14 even though some antiplatelet effects of statins are thought to be lipid dependent.…”
mentioning
confidence: 99%